2018
DOI: 10.1186/s12967-018-1543-2
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of KLF5 suppresses hypoxia-induced resistance to cisplatin in NSCLC cells by regulating HIF-1α-dependent glycolysis through inactivation of the PI3K/Akt/mTOR pathway

Abstract: BackgroundHypoxia-mediated chemoresistance has been regarded as an important obstacle in the development of cancer treatment. Knockdown of krüppel-like factor 5 (KLF5) was reported to inhibit hypoxia-induced cell survival and promote cell apoptosis in non-small cell lung cancer (NSCLC) cells via direct regulation of hypoxia inducible factor-1α (HIF-1α) expression. However, the roles of KLF5 in the development of hypoxia-induced cisplatin (DDP) resistance and its underlying mechanism in NSCLC cells remain to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 46 publications
(51 reference statements)
1
67
0
Order By: Relevance
“…demonstrated that IGF‐1 decreases radiation‐induced phosphorylation of Chk1 at S345 or S296 via the PI3K/AKT pathway . Notably, various studies have confirmed that KLF5 plays critical roles in the PI3K/Akt/mTOR pathway . Moreover, phosphorylation of Chk2 at T68 in response to DNA damage occurs in ATM‐deficient cells, suggesting that kinases other than ATM may be involved .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…demonstrated that IGF‐1 decreases radiation‐induced phosphorylation of Chk1 at S345 or S296 via the PI3K/AKT pathway . Notably, various studies have confirmed that KLF5 plays critical roles in the PI3K/Akt/mTOR pathway . Moreover, phosphorylation of Chk2 at T68 in response to DNA damage occurs in ATM‐deficient cells, suggesting that kinases other than ATM may be involved .…”
Section: Discussionmentioning
confidence: 99%
“…20 In ovarian cancer cell lines, silencing KLF5 by small interfering RNA sensitizes cells to apoptosis induced by cisplatin. 21 A previous study reported that KLF5 knockdown could suppress hypoxia-induced cisplatin resistance in NSCLC, probably via inactivation of the PI3K/Akt/ mTOR pathway; 13 however, the study failed to mention the prognostic value of KLF5 and its underlying roles in the DDR in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations